Antioxidant-Mediated Hepatoprotective Effects of Citrus aurantifolia Peels Extract in Doxorubicin-Induced Liver Injury: Acute and Sub-Acute Toxicity Assessment in Rats (Nigerian Journal of Pharmaceutical Research, 2026)
Background: The liver plays a crucial role in metabolism and detoxification but remains highly susceptible to oxidative stress induced by chemotherapeutic agents such as doxorubicin (DOX). DOX promotes the generation of reactive oxygen species (ROS), resulting in lipid peroxidation, inflammation, and hepatocellular degeneration. Medicinal plants have attracted growing interest for their potential to alleviate oxidative damage. Objective: This study aimed to evaluate the antioxidant-mediated hepatoprotective effects of Citrus aurantifolia peels extract against doxorubicin-induced liver injury in rats, alongside assessing its acute and sub-acute toxicity profile.Method: Acute and sub-acute toxicity studies were carried out in accordance with OECD guidelines. Hepatotoxicity was induced by intraperitoneal administration of DOX (15 mg/kg), followed by oral treatment with CAPE (100, 200, and 400 mg/kg) or alpha-lipoic acid (150 mg/kg) for seven days. Changes in body weight, hematological indices, and antioxidant markers (superoxide dismutase (SOD), glutathione (GSH), malondialdehyde (MDA) and Vitamins C) were assessed. Liver tissues were also examined histologically.Results: CAPE was well tolerated up to 2000 mg/kg, indicating a broad safety margin. Repeated administration at 200–400 mg/kg caused no mortality or clinical signs of toxicity, though mild lethargy was observed at 800 mg/kg. CAPE significantly (p